The Oral Microbiota May Have Influence on Oral Cancer - Zhang, Ling; Liu, Yuan; Zheng, Hua Jun; Zhang, Chen Ping (Frontiers in Cellular and Infection Microbiology, 2020)
The oral microbiota plays an important role in the human microbiota and human health, and imbalances between microbes and their hosts can lead to oral and systemic diseases, chronic inflammation which is usually caused by bacteria and contributes to cancer, and there may be a relationship between oral bacteria and oral squamous cell carcinoma (OSCC). However, these relationships have not been thoroughly characterized. Accordingly, in this study, we compared the microbiota compositions between tumor sites and adjacent normal tissues in buccal mucosal from 50 patients with OSCC using 16S rDNA sequencing. Richness and diversity of bacteria were significantly higher in tumor sites than in control tissues. Cancer tissues were enriched in six families (Prevotellaceae, Fusobacteriaceae, Flavobacteriaceae, Lachnospiraceae, Peptostreptococcaceae and Campylobacteraceae) and 13 genera, including Fusobacterium, Alloprevotella and Porphyromonas. At the species level, the abundances of Fusobacterium nucleatum, Prevotella intermedia, Aggregatibacter segnis, Capnocytophaga leadbetteri, Peptostreptococcus stomatis, and another five species were significantly increased, suggesting a potential association of these bacteria with OSCC. In addition to analyzing the diversity and composition of the oral microbiota, we profiled the functional features of the microbiota. In the tumor group, the metabolism of the microflora changed obviously, such as Lipopolysaccharide (LPS) biosynthesis, which involved in various pathological processes. Overall, oral bacterial profiles showed significant difference between cancer sites and normal tissue of OSCC patients, which might be taken as diagnostic markers and treatment targets. Our study has been registered in Chinese clinical trial registry (ChiCTR1900025253, http://www.chictr.org.cn/index.aspx).